NATO’S INTERVENTION AND JUS IN BELLO PRINCIPLES IN KOSOVO - Ladiqi, Suyatno; Musa , Nurul Izzati; Mohamed , Abdul Majid Hafiz Bin; Ahmad , Abdullahi Ayoade; Wekke, Ismail Suardi (International Journal of Psychosocial Rehabilitation, 2020)
The intervention by NATO is synonymous with its claim on humanitarian intervention in Kosovo during the Kosovo crisis in late February 1998. During the crisis, NATO attempted a military intervention based on humanitarianism mission. The alliances waged war with airstrikes rather than deploying its troops on the land. Even though such intervention lacked authorization from all members of the United Nations Security Council, NATO carried along with the strikes and managed to prevent the violation of rights on the scale of the Kosovo war and later on received notable support in the international community. The Independent International Commission states that interventions carried out by NATO in Kosovo are a category of implementing a humanitarian intervention that is considered legitimate, even if referring to the principles of international law, it can also be regarded as invalid. But the principles in jus in bello provide restrictions on just conduct during the war, which is separate from questions of who should intervene so it could help to understand these cases. This paper is to study on the issue of whether an illegal but effective intervention should be supported or should not be supported and is it permissible if it is based on humanitarian intervention and to save tens of thousands of innocent lives.